Crisis management in social media : maintaining the organizational image - Vistbacka, Sonja (2017)
The field of crisis communication has faced major changes since the expansion of internet and social media platforms. The difficulty of using social media platforms to or-ganizations’ own advantage in crisis situations has become a recent topic of discussion amongst professionals. The image of an organization provides them competitive advantage in multiple fields, so it is vital to manage these situations so the image remains positive with stakeholders. This thesis aims to provide insights for organizations on how to utilize social media in their crisis communication. 11 Finnish companies with crisis situations during the year 2016 were identified and the data was retrieved from social media platforms of Facebook, Twitter and Instagram. With Critical Discourse Analysis the utilizing of the platforms and used crisis management strategies were identified and analysed from the stakeholders’ point of view. This research first studied the theories that are considered important to the field of crisis management and crisis communication. The research questions were formed according to these theories and considered aspects such as how these organizations utilized these platforms, what crisis management strategies they executed, how the public received these attempts, and if these organizations changed their strategies due to public demand. The analysis was conducted in two ways; first the platform usage was analysed, and second, the used crisis management methods were identified. The analysis revealed that the organizations are still using mostly one-way communication in these platforms, even though they have an excellent chance for real discussion in those. Also the organizations’ crisis management strategies did not appear to include differing aspects on how to use each social media channel but rather these were treated as one in most of the cases. Practical information on how to execute crisis communication in selected social media platforms to best maintain organizations image were provided as well as suggestions for management on how to proceed with educating themselves about the possibilities and threats of social media in crisis communication.